The Chang in The Concept of Estrangement and Meaning - shoqueir, saleh; mohammed, sahar (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The importance of this research is the nature of the problem it handles , which is the phenomenon of Westernization (away from homeland) and its long term that accompanied the man since ancient times. It is not the product of a particular individual, and not the result of this day and age in particular, but rooted deep in history. The concept of Westernization is one of the most difficult concepts of what is shrouded in a lot of confusion and ambiguity due to the multiplicity of areas of use. From here this research seeks to shed light on the concept of Westernization and observes subsequent transformations and their implications. It is proven that the phenomenon of Westernization, as a comprehensive human phenomenon, is more severe in capitalist societies, a result of what it results of the tremendous economic development and social change which has led to a stark machine control and material aspect in humans. Thus the capitalist system directly contributed to strengthening the feeling of alienation and Westernization, making it a consumer society that uproots man from his origin and carries a system that he has nothing to do with it. Individuals, shall be transferred to the non-conscious group, and the Westernization of the individual case turns into a general social phenomenon.